Evaluation of the Dengue NS1 Ag StripÂ® for detection of Dengue Virus antigen in Aedes aegypti (Diptera: Culicidae) - Tan, C.H.; Wong, P.S.J.; Li, M.Z.I.; Vythilingam, I.; Ng, L.C. (Mary Ann Liebert, 2011)
Abstract Dengue fever is currently one of the most important mosquito-borne diseases that affect humans. With neither vaccines nor treatment available, prevention of the disease relies heavily on surveillance and control of mosquito vectors. In the present study, we have evaluated and showed the potential use of the Dengue NS1 Ag StripÂ® for the detection of dengue virus (DENV) in Aedes aegypti. Initial results showed that the sensitivity of the test kit in detecting DENV in wild-caught mosquitoes is comparable to that of real-time reverse transcriptaseâpolymerase chain reaction. The detection of naturally infected Ae. aegypti with the NS1 rapid test kit in our dengue cluster investigation further illustrates its potential use for surveillance of DENV in wild mosquito populations. The kit can easily be used in a simple field station, and minimal training is required. The results can be obtained in less than an hour. Employment of the kit in the field could help guide mosquito control operations in the prioritization of resources in controlling the transmission of DENV. In this study the potential of the kit for field surveillance of infected dengue vectors, which are epidemiologically important, has been demonstrated.